Plasma proteasome level is a reliable early marker of malignant transformation of liver cirrhosis. Issue 6 (6th February 2009) - Henry, L; Lavabre-Bertrand, T; Vercambre, L; Ramos, J; Carillo, S; Guiraud, I; Pouderoux, P; Bismuth, M; Valats, J-C; Demattei, C; Duny, Y; Chaze, I; et al.
Abstract : Background: Proteasomes are the main non-lysosomal proteolytic structures which regulate crucial cellular processes. Circulating proteasome levels can be measured using an ELISA test and can be considered as a tumour marker in several types of malignancy. Given that there is no sensitive marker of hepatocellular carcinoma (HCC) in patients with cirrhosis, we measured plasma proteasome levels in 83 patients with cirrhosis (33 without HCC, 50 with HCC) and 40 controls. Methods and results: Patients with HCC were sub-classified into three groups according to tumour mass. α-Fetoprotein (AFP) was also measured. Plasma proteasome levels were significantly higher in patients with HCC compared to controls (4841 (SEM 613) ng/ml vs 2534 (SEM 187) ng/ml; p<0.001) and compared to patients with cirrhosis without HCC (2077 (SEM 112) ng/ml; p<0.001). This difference remained significant when the subgroup of patients with low tumour mass (proteasome level 3970 (SEM 310) ng/ml, p<0.001) was compared to controls and patients with cirrhosis without HCC. Plasma proteasome levels were independent of the cause of cirrhosis and were weakly correlated with AFP levels. With a cut-off of 2900 ng/ml, diagnostic specificity for HCC was 97% with a sensitivity of 72%, better than results obtained with AFP. Diagnostic relevance of plasma proteasome measurement was also effective in low tumour mass patients (sensitivity 76.2% vs 57.1% for AFP). Conclusion: The plasma proteasome level is a reliable marker of malignant transformation in patients with cirrhosis, even when there is a low tumour mass.